Affective Practices of Diabetes Self-Management Among Older Adults: Cumulative Effects of Childhood Adversity. (18th August 2021) - Roth, Erin G; Chard, Sarah
Abstract: Background and Objectives: A strong correlation exists between Type 2 diabetes mellitus and adverse childhood experiences. How adverse childhood experiences inform later-life diabetes management is less understood. This article examines diabetes management from the perspective of affective practice to explore the lingering impact of trauma biographies in diabetes management. Research Design and Methods: This secondary narrative analysis of 15 in-depth interviews with community-dwelling older adults with diabetes (subsample of the Subjective Experiences of Diabetes Study) focuses on the ways their reported childhood adversity affects perceptions of and responses to diabetes self-management. Results: The experiences of adversity in childhood accumulate, throughout the life course, in the affective practices informing diabetes self-management, from blood glucose testing, to food consumption, to the emotions invested in body size. We identify 3 thematic areas that emerged across participants: (a) undermining self-worth, (b) (over)eating and food as comfort, and (c) weight and body size. Discussion and Implications: Our findings highlight affective practices as a mechanism through which adverse events accumulate and shape well-being over the life course. This analysis also suggests the potential for (de)accumulation of affective practices to improve diabetes management. The findings support recent calls for trauma-informed clinical care.